Treasure Island : runaway gold - Rhodes, Jewell Parker (Quill Tree Books, an imprint of HarperCollinsPublishers, 2023)
Zane is itching for an adventure that will take him away from his family's boarding house in Rockaway, Queens. So when he is entrusted with a real treasure map, leading to a spot somewhere in Manhattan, Zane wastes no time in riding the ferry over to the city to start the search with his friends Kiko and Jack and his dog, Hip-Hop. Through strange coincidence, they meet a man who is eager to help them find the treasure: John, a sailor who knows all about the buried history of Black New Yorkers of centuries past, and the gold that is hidden somewhere in those stories. As a vicious rival skateboard crew follows them around the city, Zane and his friends begin to wonder who they can really trust. And soon it becomes clear that treasure hunting is a dangerous business.